Результати використання технології RELEX SMILE у пацiєнтів з міопічною рефракцією - Завгородня, Наталія Григорівна; Завгородня, Т. С.; Поплавська, Ірина Олександрівна; Zavgorodnya, N. G.; Zavgorodnya, T. S.; Poplavska, I. O. (My University, 2021)
Мета. Вивчити результати лазерної корекції зору у пацієнтів з міопією та складним міопічним астигматизмом із застосуванням технології ReLEx SMILE. The study was conducted to investigate the results of laser vision correction in patients with myopia and compound myopic astigmatism using ReLEx SMILE technology. The results of laser vision correction using ReLEx SMILE technology in 43 patients (82 eyes) were analyzed. All eyes were diagnosed with myopia and compound myopic astigmatism: 33 eyes (40.2%) showed mild myopia, 45 eyes (54.9%) - moderate myopia, and others - high myopia (4.9 %). On the first day after the laser correction ReLEx SMILE, the expected visual acuity was noted in 74 eyes (90.2. Full adaptation of the corneal incision and epithelialization in the access area was evident. As a result, of the intervention a month later, the maximum corrected visual acuity was achieved in 98.8%, and autorefractometry indicators were from +0.25 to -0.25 d, which allows to recommend this type of vision correction as a method of choice in patients with myopic refraction.
Results of the use of RELEX SMILE technology in patients with myopic refraction